2018
DOI: 10.7150/ijms.27489
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Japanese rice-koji miso extracts on hepatitis A virus replication in association with the elevation of glucose-regulated protein 78 expression

Abstract: Hepatitis A virus (HAV) infection is one of the major causes of acute hepatitis and acute liver failure in developing and developed countries. Although effective vaccines for HAV infection are available, outbreaks of HAV infection still cause deaths, even in developed countries. One approach to control HAV infection is prevention through diet, which can inhibit HAV propagation and replication. Glucose-regulated protein 78 (GRP78) is a member of the heat shock protein 70 family of molecular chaperone required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…117,118 Accordingly, both PHH and HLCM-derived human hepatocytes are capable of supporting the viral lifecycle of HAV in vitro. 119,120 This evidence strongly encourages us to consider employing HLCM as an in vivo study model of HAV infection.…”
Section: Hepatitis a Virusmentioning
confidence: 93%
“…117,118 Accordingly, both PHH and HLCM-derived human hepatocytes are capable of supporting the viral lifecycle of HAV in vitro. 119,120 This evidence strongly encourages us to consider employing HLCM as an in vivo study model of HAV infection.…”
Section: Hepatitis a Virusmentioning
confidence: 93%
“…Japanese rice-koji miso extracts enhanced GRP78 expression and inhibited HAV HA11-1299 genotype IIIA strain replication in the human hepatocytes, Huh7 and PXB cells [ 97 ]. We investigated the effect of miso extracts on virus replication in HepG2.2.15 cells infected with the HAV HA11-1299 strain [ 73 ].…”
Section: Prevention Of Hav Infection In Patients With Chronic LIVmentioning
confidence: 99%
“…Koji, also known as Aspergillus oryzae, is a filamentous fungus employed by the Japanese to ferment certain kinds of food like soybeans, potatoes, rice and some other grains [71]. Miso is one of the by-products of the fermentation of Japanese rice by Koji.…”
Section: Adjunctive Anti-hav Natural Products 31 Japanese Rice-koji mentioning
confidence: 99%
“…Miso is one of the by-products of the fermentation of Japanese rice by Koji. Miso is conventional Japanese seasoning used for preparing miso soup, a staple Japanese cuisine [71]. Previous studies showed that Japanese miso extract increases the expression of a heat-shock protein known as glucose-regulated protein 78 (GRP78) and suppresses ultraviolet C mutagenesis [72].…”
Section: Adjunctive Anti-hav Natural Products 31 Japanese Rice-koji mentioning
confidence: 99%
See 1 more Smart Citation